PENGARUH PERTUMBUHAN LABA, UKURAN PERUSAHAAN DAN REPUTASI KAP TERHADAP KUALITAS LABA - Sari, Medina Anggita; Ginting, Rudi; Nopiyanti, Anita (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2021)
This research is a quantitative research aimed to determine the effect of earnings growth, firm size, and reputation of KAP on earnings quality. This study uses data from manufacturing companies listed on the Indonesia Stock Exchange 2016-2017 with purposive sampling methods. The researcher used 63 companies from 148 companies that experienced profit growth during the study period. Secondary data in the observation period originated from the company's annual Financial Statements that have been published. The hypothesis test used is Multiple Regression Analysis by the Program and Service Solution (SPSS) version 25 statistic with a significance level of 5%. The results of the study show that earnings growth, company size and KAP reputation do not significantly influence earnings quality.